Safe use of statins: focus on muscle toxicity. (1st December 2016) - Kolovou, Vana; Bilianou, Helen; Kolovou, Genovefa
Abstract: Muscle toxicity can be classified as myopathy, myalgia, myositis or rhabdomyolysis (RM). RM can occur in patients with muscular dystrophy, alcoholic myopathy, peripheral artery disease and myocardial infarction as well as prolonged convulsions or immobility. Also, RM can occur, in otherwise healthy individuals, after viral illness, crush or high-voltage electrical injury, hyperthermia, severe exercise and taking certain drugs, particularly 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase inhibitors (statins). Muscle disorders provoked by statin use have been named "statin-associated myopathy (SAM)". There is no commonly accepted definition of SAM, although recently a score system was introduced and the European Atherosclerosis Society (EAS) proposed a definition of SAM. There are several possible explanations for SAM; for example, genetic predisposition, decreased intracellular cholesterol levels, reduced production of coenzyme Q10 and related ubiquinones and decreased production of prenylated proteins. Due to the widespread use of statins, it is very important to diagnose SAM and particularly its severe presentation, RM. Early treatment will prevent serious complications. This review will focus on SAM.